Academic Life in Contemporary Indonesia: Inequality, Repression, and the Illusion of Freedom - Dhoni Zustiyantoro (Centre for Literary and Cultural Studies, 2026)
To be an academic in Indonesia today is to work within an increasingly acute paradox. On the one hand, national law recognises academic freedom, the freedom of the academic rostrum, and scholarly autonomy as essential elements of higher education. Law No. 12 of 2012 on Higher Education, for instance, defines academic freedom as the freedom of the academic community to pursue and develop knowledge through education, research, and community service (Republik Indonesia, 2012). On the other hand, the lived experiences of many lecturers, researchers, and students suggest that such freedom is often conditional. Academics appear to be free so long as they do not challenge power, touch particular economic-political interests, criticise the security apparatus, or disturb the government’s public image. This condition may be understood as a form of “illusory freedom”: freedom that exists as a legal norm, yet remains fragile as a socio-political practice.